A latent class analysis of alcohol and posttraumatic stress symptoms among offspring of parents with and without alcohol use disorder. (January 2021) - Bender, Annah K.; Meyers, Jacquelyn L.; di Viteri, Stacey Subbie-Saenz; Schuckit, Marc; Chan, Grace; Acion, Laura; Kamarajan, Chella; Kramer, John; Anohkin, Andrey; Kinreich, Sivan; Pandey, Ashwini; Hesselbrock, Victor; et al.
Highlights: Parent AUD is associated with offspring trauma exposure, AUD and PTS symptoms. Latent class analysis can empirically test typologies of subclinical comorbid AUD-PTSD. Understanding sublinical AUD-PTSD may guide research and clinical practice. Abstract: The co-occurrence of posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) is widely known, yet few studies have examined whether and how AUD symptoms co-occur with PTSD symptom clusters of hypervigilance, avoidance/numbing, and re-experiencing. The purpose of this study was to examine potential overlap between AUD and posttraumatic stress symptomatology, and to characterize the resultant latent classes in terms of demographics, drinking behaviors, parental AUD, and specific traumas experienced (physical violence, sexual violence, and non-assaultive trauma). We hypothesized that classes would be differentiated by type and severity of AUD and PTS symptoms. Drawing from a sample of white and Black participants from the Collaborative Study on the Genetics of Alcoholism (COGA), we examined young adults between the ages of 18–35 who had experienced trauma (N = 2478). A series of LCA models based on the type of trauma experienced, posttraumatic stress symptoms and problematic alcohol use were then fitted to the data. A four-class solution provided the best fit, consisting of a low symptom class (N = 1134), moderate alcohol/low PTS severity (N = 623), mild alcohol/high PTS severity (N = 544), and high symptom severity (N = 177). Higher prevalence of sexual assault was associated with membership in high PTS severity classes, and parent AUD was associated with membership in each class, particularly when the mother or both parents had the disorder. Using person-centered methods such as LCA is a commonsense approach to understanding the heterogeneity of symptoms, trauma types, and individual-level characteristics associated with trauma-exposed individuals and comorbid AUD-PTSD, and our study is one of relatively few to empirically ascertain the co-occurrence of alcohol and PTS symptoms in a high-risk family sample.